A randomized, double‐blind, phase III, multicentre study to evaluate the safety and efficacy of BF‐200 ALA (Ameluz®) vs. placebo in the field‐directed treatment of mild‐to‐moderate actinic keratosis with photodynamic therapy (PDT) when using the BF‐RhodoLED® lamp. (1st October 2016) - Reinhold, U.; Dirschka, T.; Ostendorf, R.; Aschoff, R.; Berking, C.; Philipp‐Dormston, W.G.; Hahn, S.; Lau, K.; Jäger, A.; Schmitz, B.; Lübbert, H.; Szeimies, R.‐M.
Summary: Background: Multiple actinic keratosis (AK) lesions may arise from the cancerization of large, sun‐damaged skin areas. Although photodynamic therapy (PDT) is considered the most effective therapeutic option, the efficacy and safety of field treatment of multiple AK lesions with PDT has never before been tested in a pivotal trial. Objectives: To evaluate the efficacy, safety and cosmetic outcome of BF‐200 ALA (a nanoemulsion formulation containing 10% aminolaevulinic acid hydrochloride) combined with the BF‐RhodoLED ® lamp for the field‐directed treatment of mild‐to‐moderate AK with PDT. Methods: The study was performed as a randomized, multicentre, double‐blind, placebo‐controlled, parallel‐group, phase III trial with BF‐200 ALA and placebo in seven centres in Germany. A total of 94 patients were enrolled in this study; 87 were randomized (55 patients received BF‐200 ALA, 32 received placebo). Patients received one PDT. If residual lesions remained at 3 months after treatment, PDT was repeated. Illumination was performed with the PDT lamp BF‐RhodoLED (635 nm ± 9 nm) until a total light dose of 37 J cm −2 was achieved. Results: BF‐200 ALA was superior to placebo with respect to patient complete clearance rate (91% vs. 22%, P < 0·0001) and lesion complete clearance rate (94·3% vs. 32·9%, P < 0·0001) after a maximum of two PDTs. The confirmatory analysis of all key secondary variables supported this superiority" should not be skipped since this is an important result. Treatment‐emergent adverse events (TEAEs) were experienced by 100% of the BF‐200 ALA group and 69% of the placebo group. The most commonly reported TEAEs were TEAEs of the application site. The cosmetic outcome was improved in the BF‐200 ALA group compared with placebo. Conclusions: Field‐directed therapy with BF‐200 ALA and BF‐RhodoLED lamp is highly effective and well tolerated for multiple mild‐to‐moderate AK lesions, providing greatly improved skin quality.